Agrarian Modernization of the Kharkіv Province: the View of a Foreigner (in the 1860s) - Лисенко, Майя (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2018)
In the article the problem of modernization of agrarian sphere of the Kharkiv province is investigated. An analysis of changes in the agricultural sector of the region was made by a foreign citizen F. I. Geyduk. A well-known agrarian explained the reasons for the difficulties in implementing reforms. He pointed out ways to overcome the crisis and a means to improve the situation in agriculture. Using European experience and cooperation of Kharkiv landowners with foreigners contributed to the success of local producers and attached the population to the best achievements of the Czechs. In general, the ideas of F. I. Geyduk were implemented in theprovince